DETERMINATION OF ISOTOPIC RATIO OF D/H, 12C/13C, 14N/15N, 16O/17O, AND 16O/18O ON TITAN'S ATMOSPHERE USING ALMA RADIO TELESCOPE - Apricilia
Titan is the largest satellite of Saturn and is the only satellite in the Solar System that has a thick atmosphere. The chemical composition of Titans atmosphere that is very rich in organic molecules has been intensively studied through ground-based and space-based observations, e.g., by Voyager and Cassini Missions. Observations of chemical compounds and their isotopologues may lead to the determination of their isotopic ratios. The values of isotopic ratios are key information and are important to derive the process of creation and evolution occuring in a particular object. This is based on the Solar System formation theory which states that the Solar System began with the gravitational collapse of a small part of giant molecular cloud. Hence, the Solar System must originate from a common material disk. Consequently, by knowing the difference between the isotopic ratios of an object to its standard value, we might learn about the difference of the evolution mechanism happening on that object. This Final Project undertakes data processing and analyses a set of data from observations of Titan taken by ALMA radio interferometer to determine the isotopic ratio of 14N/15N, 16O/17O, 16O/18O, 12C/13C, and D/H using HCN and CO from Titans atmosphere. The isotopic ratio values are 14N/15N = 72 and 14N/15N = 75, 16O/17O = 2917, 16O/18O = 497, 12C/13C = 88,9, 12C/13C = 89, 12C/13C = 110 and 12C/13C = 122, and D/H = (3,31306991-3,34140436) x 10-4. Error analyses were not carried out thoroughly, but the uncertainties on calibration errors affecting the results were estimated to be 10%.